Implementation of Human Resources Management in Achieving the Vision of The Muhammadiyah Boarding School Tangerang Institution - Hermawan, Endang; Khan, Rahul (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2023)
The research determines the implementation of human resource management in achieving the institutional vision at Muhammadiyah Boarding School Tangerang, and the factors that support and hinder the achievement of the institutional vision. The research method used is a qualitative descriptive approach. Data collection techniques include observation, interviews, and documentation. Data analysis uses the Miles and Huberman interactive analysis model, namely data reduction, data presentation, verification, and conclusions. The result is: (1). Implementation of human resource management through planning, recruitment and placement, training and development, and evaluation, (2). Factors supporting and hindering implementation in achieving the institution's vision are due to lack of coordination in planning, human resources not meeting the qualifications in employee recruitment, limited training time in human resource development, not yet focused on implementation, evaluation not yet regular, there is no supervisory team (3). The solution to overcome obstacles is to increase coordination between the Director, head of the madrasah, and related parties, and synchronize schedules in evaluating and monitoring HR performance.